Obsolescence of Physics Literature Cited in the Doctoral Dissertations of University of Kerala - Pillai Sudhier, K. G. (Journal of Information and Knowledge, 2007)
The obsolescence and aging studies are important areas of citation analysis in Library and Information science. The paper attempts to examine the obsolescence of literature in Physics by citation analysis and reviewed various studies already done in the field and outlined the results. The study is based on the 3,180 citations, cited in the 12 doctoral dissertations of Physics awarded from Department of Physics, University of Kerala, India during the period of 1999-2003. It is observed that journals and books are the most preferred bibliographic form of citations used by the Physicists, and they occupy 82.08% and 12.92% respectively. The findings show that the half-life of journal citations was 14 years and for books it was 25 years. The mean year of journals was calculated as 17.58 and 23.09 years for the books.